The Effect of Brainstorming Method on Giving Exclusive Breastfeeding to Attitudes, Subjective Norms, Perceived Behavioral Control, and Breastfeeding Intention Among Pregnant Women - Dyah Rohmatussolichah; Mira Triharini; Nadia Rohmatul Laili (Universitas Airlangga, 2020)
Introduction: Breastfeeding behavior is effected by breastfeeding intention. The intention of breastfeeding is formed by three main factors, which are attitude, subjective norms, and perceived behavioral control. The purpose of this study was to analyze the effect of health education with a brainstorming method about exclusive breastfeeding toward attitude, subjective norms, perceived behavioral control, and mother's intention on giving exclusive breastfeeding.Methods: This study used a quasi-experiment with a pretest-posttest of control group design. The variables in this study were brainstorming method, attitude, subjective norms, perceived behavioral control, and breastfeeding intention. The population of this study was second and third-trimester pregnant women at the working area of the public health center in Klampis Ngasem and Pacarkeling Surabaya, with 48 respondents selected using simple random sampling. The instrument used a questionnaire and analyzed using Wilcoxon Signed Rank and Mann Whitney U test with significance values α=0,05.Results: The Wilcoxon Signed Rank test showed significant differences in the attitudes (p=0.000), subjective norms (p=0.000), perceived behavioral control (p=0.000), and intentions (p=0.000) before and after brainstorming intervention. Mann Whitney U post-test showed significant differences in the attitudes (p=0.000), subjective norms (p=0.000), perceived behavioral control (p=0.000), and intentions (p=0.000) between treatment and control group.Conclusion: The intervention of health education with the brainstorming method has a significant effect of increasing attitude, subjective norms, perceived behavioral control, and mother's intention on giving exclusive breastfeeding. Further research should be to analyze the impact of brainstorming toward breastfeeding intention in postpartum mothers.